Women’s empowerment in water governance in Polder Zone in Bangladesh - Sarker, Mou Rani; Singaraju, Niyati; Batas, Mary Ann; Mondal, Manoranjan K.; Das, Mahanam; Puskur, Ranjitha; Yadav, Sudhir (International Rice Research Institute, 2023)
The polders in coastal zones of Bangladesh are vulnerable to climate risks resulting in low agricultural 3.50-5.00 DAY 2 · Tuesday, October 10 · Parallel sessions productivity and low incomes for the communities dependent on agriculture-based livelihoods in these regions. Bangladesh adopted a participatory approach to water governance in the 1980s to improve the equitable and sustainable use of water resources. With men migrating away for better income opportunities, women are more involved in agricultural production and dependent on water resources. However, there is limited evidence on the implications of participatory water management on women’s empowerment outcomes—whether it results in improved participation and agency of women in farm production and control over farm incomes. Addressing this gap, drawing data from 640 households in four polders of Patuakhali district using a mixed-methods approach, the study aims to examine the implications of participatory water management on women’s empowerment outcomes in three domains—agency, resources, and institutional structures adopted from the Empowerment in Water, Sanitation and Hygiene (WASH) framework. The findings reveal that women’s agency outcomes improved with increased participation in joint decisionmaking and mobility. Women still had limited access to productive resources and control over farm incomes. Nevertheless, their access to credit and agricultural technology improved due to WMGs. The policies and interventions remained gender insensitive as they did not address the prevailing social barriers and pervasive cultural norms, thus exacerbating the existing gender inequalities in society. Therefore, we argue that unless the structural barriers are addressed, participatory water governance would not empower women in polder zones.